Aproveitamento energético do biossólido gerado por indústria têxtil como fertilizante para produção de capim-elefante – Cenchrus purpureus (Schumach.) Morrone - Neves, Talles Iwasawa (2017)
Sludge generated by effluent treatment plants was normally disposed of in landfills, which, as of August 2014, was banned in Brazil. Therefore, its utilization becomes necessary. Due to its good composition of nutrients and organic matter, sludge is called biosolid, and its use as agricultural fertilizer is quite feasible. For the present work, an experiment was conducted at an experimental farm in Pedras de Fogo / PB, where the objective was to compare the production of elephantgrass - Cenchrus purpureus (Schumach.). Morrone - physical-chemical gains and losses in the soil and the evaluation of the life cycle of the fertilizer application, through a randomized block design with three blocks, where the treatments consisted of: no fertilization, conventional fertilization, 1 x, 2 x, 4 x and 8 x Resolution of CONAMA. The feasibility of the application of biosolids as fertilizer was verified, provided that it is made according to the Conama Resolution 375/06. In this dosage, elephant grass production, on average, was similar to treatments with chemical fertilization, increasing nutrients to the soil, without causing any type of contamination to the same. According to the Life Cycle Assessment (LCA) study, it was observed that the dosage of biosolids according to the Conama Resolution 375/06, presented approximately 32.3% less in CO2 emissions equivalent to than the recommended chemical fertilizer dosage.